2015
DOI: 10.1371/journal.pone.0120250
|View full text |Cite
|
Sign up to set email alerts
|

TORC1 Promotes Phosphorylation of Ribosomal Protein S6 via the AGC Kinase Ypk3 in Saccharomyces cerevisiae

Abstract: The target of rapamycin complex 1 (TORC1) is an evolutionarily conserved sensor of nutrient availability. Genetic and pharmacological studies in the yeast Saccharomyces cerevisiae have provided mechanistic insights on the regulation of TORC1 signaling in response to nutrients. Using a highly specific antibody that recognizes phosphorylation of the bona fide TORC1 target ribosomal protein S6 (Rps6) in yeast, we found that nutrients rapidly induce Rps6 phosphorylation in a TORC1-dependent manner. Moreover, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 34 publications
4
98
0
1
Order By: Relevance
“…We shifted WT and set2 Δ cells from nutrient rich (YPD) medium to medium lacking amino acids (SD) and collected samples every 30–60 minutes over a 2-hour time period. We examined the protein and phosphorylation levels of Rps6, the Saccharomyces cerevisiae S6K homolog (Gonzalez et al, 2015), a key downstream target of TORC1. As shown in Figure 3D, the level of Rps6 was much lower in set2 Δ cells compared with their isogenic WT counterparts, and, further, Rps6 had a drastically increased level of phosphorylation at the start of the time course, continuing through 30 minutes after nutrient stress.…”
Section: Resultsmentioning
confidence: 99%
“…We shifted WT and set2 Δ cells from nutrient rich (YPD) medium to medium lacking amino acids (SD) and collected samples every 30–60 minutes over a 2-hour time period. We examined the protein and phosphorylation levels of Rps6, the Saccharomyces cerevisiae S6K homolog (Gonzalez et al, 2015), a key downstream target of TORC1. As shown in Figure 3D, the level of Rps6 was much lower in set2 Δ cells compared with their isogenic WT counterparts, and, further, Rps6 had a drastically increased level of phosphorylation at the start of the time course, continuing through 30 minutes after nutrient stress.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, strains were grown in flasks containing 50 ml of YMM + Pro medium until OD 600 ~ 0.8, and then 700 μl of glutamine (25 mg/ml; 0.5 mg/ml final concentration) was added. Samples were taken at different time points (0, 5, 15, and 30 min) to perform protein extraction and subsequent immunoblot as previously described (Gonzalez et al, ). To evaluate Sch9 phosphorylation, cell extracts were subjected to chemical cleavage with 2‐nitro‐5‐thiocyanatobenzoic acid (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent research showed that Rps6 phosphorylation is completely abolished in cells lacking Ypk3, another AGC kinase, and expression of human S6K in ypk3Δ cells restores Rps6 phosphorylation in a rapamycin‐sensitive manner. The results indicated that Ypk3 is the functional ortholog of mammalian S6K .…”
mentioning
confidence: 94%